Acute Intrathoracic Tuberculosis in Children and Adolescents with Community-Acquired Pneumonia in an Area with an Intermediate Disease Burden (2022)
ABSTRACT: Tuberculosis (TB) in the pediatric population is a major challenge. Our objective was to describe the clinical and microbiological characteristics, radiological patterns, and treatment outcomes of children and adolescents (from 1 month to 17 years) with community-acquired pneumonia (CAP) caused by TB. We performed a prospective cohort study of a pediatric population between 1 month and 17 years of age and hospitalized in Medellín, Colombia, with the diagnosis of radiologically confirmed CAP that had ≤ 15 days of symptoms. The mycobacterial culture of induced sputum was used for the bacteriological confirmation; the history of TB contact, a tuberculin skin test, and clinical improvement with treatment were used to identify microbiologically negative TB cases. Among 499 children with CAP, TB was diagnosed in 12 (2.4%), of which 10 had less than 8 days of a cough, 10 had alveolar opacities, 9 were younger than 5 years old, and 2 had close contact with a TB patient. Among the TB cases, 50% (6) had microbiological confirmation, 8 had viral and/or bacterial confirmation, one patient had multidrug-resistant TB, and 10/12 had non-severe pneumonia. In countries with an intermediate TB burden, Mycobacterium tuberculosis should be included in the etiological differential diagnosis (as a cause or coinfection) of both pneumonia and severe CAP in the pediatric population.